STUDY OF KARYOTYPE AND NUCLEOLAR ORGANIZER REGIONS (NORS)IN WILD, SYNTHETIC AND CULTIVATED WHEATS - Arabbeigi, M.; Arzani, A.; Saeidi, G. (Emirates Journal of Food and Agriculture, 2011)
Wild relatives of bread wheat are potential sources of valuable genetic materials for wheat improvement. Karyotype analysis plays an important role in the identification and designation of chromosomes in many plant species. In this study, the karyotype features and nucleolar organizer regions (NORs) of 21 wheat genotypes representing diploid, tetraploid and hexaploid species and belonging to wild, cultivated and synthetic groups were investigated. Total chromosome length (TCL) values vary across the genotypes. The highest value (99.1 µm) was recorded in one of a synthetic hexaploid wheat (Doy1/ Ae. squarrosa (458)) with a mean chromosome length (MCL) of 5.67±0.59 µm, while the lowest value (39.48µm) was found in T. monococcum species with a mean chromosome length (MCL) of 4.06±0.51 µm. Cluster analysis based on chromosomal characteristics and karyotype asymmetry indices including symmetry index (S %), total form percentage (TF %), Romero-Zarco's indices (A1and A2) and Stebbin's classification divided the genotypes into three groups. Results revealed that group 1, including synthetic hexaploid wheat accessions, had the most asymmetric karyotype in terms of centromere position and chromosome length. Ag-NOR banding identified two nucleolus organizer regions (NORs) on the long arms of the chromosomes 1B and 6B in both tetraploid and hexaploid wheats.